PENERAPAN MODEL LINEAR PROGRAMMING UNTUK MENGOPTIMALKAN JUMLAH PRODUKSI DALAM MEMPEROLEH KEUNTUNGAN MAKSIMAL (Studi Kasus pada Usaha Angga Perabot) - Dewi Rosa Indah; Purnita Sari (Jurnal Manajemen Inovasi, 2019)
Abstract This study aims to determine the optimal amount of production and maximum profits in Angga Furniture. The data analysis method uses linear programming with calculations using QM POM. Research results based on research profit = 450,000 TT + 300,000 L + 275,000MR Raw material constraints: 5.5 + 4,5 + 3,5 4,5 6,048, work hour agreement: 18 + 20 + 11 ≤ 21,916, Quantity X1 ≥ 0, cotton X2 ≥ 0, number of X3 ≥ 0. Production of beds is 1,099,636 units (optimal value is 1,099,636). Cabinets and dressing tables remain with the same production because they do not produce optimal value. The value of reducing costs for a bed is worth 0 (has no reduced costs), the value of reducing costs is 306.82 m3, the value of reducing the cost of a dressing table by 39.77m3. From the use of three types of products then for the bed has a value of slack / residual of 0. Cabinets and dressers have not been able to increase profits. The remaining work hours are 2,122,554 to produce beds, cabinets and dressing tables. Keywords Production, Maximum Advantage, Linier Programming.